The Effects of Physical Exercise on the Quality of Life of Healthy Older Adults in China: A Systematic Review - Wei, Lin; Hu, Yongmei; Tao, Yingying; Hu, Rui; Zhang, Liancheng (Frontiers in Psychology, 2022)
Objective: To systematically evaluate the effects of physical exercise on the quality of life of healthy older adults in China. Methods: Information was retrieved from CNKI, Wanfang, China Science and Technology Journal Database, PubMed, EBSCO, Web of Science and Library of Congress. They were published up until December 2022. Inclusion criteria: the study subjects were healthy Chinese older adults (age ≥ 60), the sample size was clear, the study was included in a randomized controlled or investigational study. The study reported using at least one quality of life questionnaire, and included at least one physical exercise. Results: 19 studies met the inclusion criteria, including 6 studies in the intervention group using single physical exercise type and 13 studies using comprehensive physical exercise type. All the 19 studies adopted the form of intervention group and control group, 12 (63%) were investigative studies and 7(37%) were experimental studies, among which 5 studies were positive control group and 2 were negative control group. All 19 studies reported that physical exercise had different degrees of positive effects on the quality of life of the older adults. Psychosomatic exercise can effectively improve the physical and mental health of the older adults, and aerobic exercise only have a positive effect on physical health. Compared with no exercise or other exercise, the exercise group in the survey had a positive effect on the quality of life of older adults. Regardless of the form of control group, the exercise group in the experimental study both had a positive effect on the quality of life of older adults. Conclusion: Physical exercise has a positive impact on the quality of life of healthy older adults. Due to the wide and mixed scope of the included studies, and to further illustrate the effect, more randomized controlled trials should be included in future studies to examine differences in item, intensity, duration, and frequency.